KONSTRUKSI MAKNA PEREMPUAN BERHIJAB VERSI COVER MAJALAH SCARF - Aisyah, Novrisa Nu; Hafiar, Hanny; Novianti, Evi (EDUTECH, 2018)
Abstract. Muslim lifestyle in the city which one of the causes is the development of mass me-dia, especially in religious nuances magazines. By analyzing 13rd â€“ 18th volume of SCARF Maga-zine Cover this research is done to find out how the Scarf magazine constructs hijaber in their cover magazine version. The method used in this study is a qualitative method with Peirce semiot-ics analysis and data collection techniques in this study is by Interview, Observation, and Library Studies. From the results of this study found that there are ten symbols on the cover of Scarf maga-zine that has a meaning in accordance with the criteria of muslimah urban Scarf magazine. The ten symbols are models are public figure, entrepreneur models symbol, a gesture tilting his head, a gesture raising one foot, hand closing gesture, a fashion symbol, a hijab headscarf, a symbol of wearing a headscarf, a symbol of different makeup styles - different, and SCARF text symbols. Where the meaning is to construct hijabers in version of Scarf magazine cover. The conclusion of this research is that the symbols have a meaning that construct a muslimah in magazine cover of Scarf magazine not only through fashion but also from other symbols that fit with the characteris-tics of Muslim according to the magazine that is smart, active, independent, confident, dynamic, and commit to spirituality value. From this research SCARF should more consider about spiritual-ity value and other symbol that shown through the cover magazine according to the vison of this magazine.Â Abstrak. perkembangan hijab bagi muslimah di kota besar salah satunya diakibatkan perkembangan media massa khususnya majalah bernuansa agama termasuk majalah SCARF. Dengan menganalisis Cover majalah SCARF volume 13-18 penelitian ini bertujuan untuk menge-tahui bagaimana majalah SCARF mengkonstruksi perempuan berhijab versi cover majalahnya. Metode yang digunakan yaitu metode penelitian kualitatif dengan analisis semiotika Charles Sand-ers Peirce dan teknik pengumpulan data Wawancara, Observasi, dan Studi Pustaka. Dari hasil penelitian didapatkan bahwa terdapat sepuluh simbol pada cover majalah Scarf yang memiliki makna sesuai dengan kriteria muslimah urban mengkonstruksi perempuan berhijab versi cover majalah Scarf. Sepuluh simbol tersebut yaitu simbol model seorang public figure, simbol model seorang entrepreneur, simbol gesture mendongakkan kepala, simbol gesture meninggikan satu ka-ki, simbol gesture tangan menutup, simbol gaya busana, simbol jilbab tidak menutup dada, simbol penggunaan jilbab, simbol gaya riasan yang berbeda-beda, dan simbol teks SCARF. Simpulan dari penelitian ini simbol-simbol tersebut memiliki makna yang mengkonstruksi perempuan berhijab versi cover majalah Scarf tidak hanya melalui fashion tapi juga dari simbol lain yang sesuai dengan karakteristik muslimah menurut majalah tersebut yaitu smart, active, independent, confi-dent, dynamic, dan commit to spirituality value. Pada penelitian ini peneliti menyarankan agar majalah SCARF lebih mempertimbangkan simbol-simbol termasuk nilai-nilai spiritual yang di-tunjukkan melalui covernya agar lebih sesuai dengan tujuan majalah.